Investment Value Tauhid on Primary Student Through Realistic Mathematics Education Based on Indigenous System - Wihaskoro, Ahmad Mabruri; Komalasari, Mahilda Dea (Proceeding International Conference on Science and Engineering, 2019)
The learning process in primary school is an effective foundation of education in the investment of tauhidism values. Tauhid is the Islamic foundation of individuals. An individual who is strong in tauhidism will get the salvation of the world and the hereafter. The characteristics of the people who have tauhid are (1) faith and fear of Allah, and knowledgeable; (2) responsible; and (3) noble character. The effort to the investment the value of tauhidism should not only be taught in the subjects of Islam but also must be integratedinterconnected with other subject matter in general, including in mathematics subjects. One approach to investing the value of tauhidism in mathematics subjects is realistic mathematics education based on indigenous system. Realistic mathematics education based on indigenous system is a teaching and learning approach that is able to accommodate various concepts of tauhidism to be taught to primary students through discussion of problems based on the reality of local wisdom where the student lives. The preparation of this paper aims to review the literature in the application of realistic mathematics education based on indigenous system that can be used as a model to investing tauhid values in primary school students. The scope of this paper, i.e. : (1) the concept of realistic mathematics education based on indigenous system shapes students' self-awareness of the values of tauhidism; and (2) students are able to invest their tauhid values not only in classroom learning but also in students' daily lives.